MENGEMBANGKAN KOGNITIF DAN MOTORIK ANAK USIA DINI MELALUI HAFALAN HADITS DENGAN GERAKAN - Fitriya, Anita (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2025)
Early Childhood Education Learning Process Is a part of pre-school education whose learning is directed at the development of students. Early childhood education occupies a significant position because this period is the determining age, therefore it is called the (Golden Age). Efforts to improve the quality of early childhood education so that it runs optimally require interesting and educational learning strategies in stimulating the development of early childhood, especially in motoric and cognitive development. The focus of this study is classified into three parts, 1) How are the steps in developing cognitive and motoric early childhood through memorization of hadith with movement, 2) What is the impact of memorization of hadith based on movement on early childhood. The research approach uses qualitative and the type of research design is based on case studies. In this study, researchers used the Purposive Sampling technique to determine informants. Data collection techniques in this study were participant observation, semi-structured interviews, and documentation. Data analysis used the Miles & Huberman qualitative research model, namely: a. Data reduction, b. Data presentation (data display) c. Drawing conclusions (verification). The results of the study indicate that 1) the steps to develop cognitive and motor skills of early childhood through memorizing hadith with movement are the preparation of hadith in RPPH, implementation in the classroom and evaluation after the end of learning. 2) The impact of memorizing hadith based on movement a) makes it easier for children to memorize, b) gets children used to always behaving well and is applied in everyday life. c) balances the right brain and left brain of children. d) and develops children's cognitive and physical motor skills e) children are more enthusiastic in memorizing.